2020
DOI: 10.1016/j.cels.2020.06.005
|View full text |Cite
|
Sign up to set email alerts
|

PertInInt: An Integrative, Analytical Approach to Rapidly Uncover Cancer Driver Genes with Perturbed Interactions and Functionalities

Abstract: SUMMARY A major challenge in cancer genomics is to identify genes with functional roles in cancer and uncover their mechanisms of action. We introduce an integrative framework that identifies cancer-relevant genes by pinpointing those whose interaction or other functional sites are enriched in somatic mutations across tumors. We derive analytical calculations that enable us to avoid time-prohibitive permutation-based significance tests, making it computationally feasible to simultaneously consider m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 86 publications
0
11
0
Order By: Relevance
“…While de novo DNA-binding specificity prediction is necessary for predicting binding preferences of completely uncharacterized TFs, in the context of natural variation and disease, there is great interest in predicting the changes in DNA-binding specificities induced via single-amino acid alterations to wildtype TFs. Mutated TFs are seen in cancer (Kobren et al 2020), and in inherited diseases (Hamosh et al 2005;Chi 2006). If such an alteration occurs in a DNA-contacting residue, as a first approximation, de novo prediction is necessary only for the binding site positions contacted by that altered residue, while the specificity for the remaining binding site positions can be transferred directly from the wildtype.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…While de novo DNA-binding specificity prediction is necessary for predicting binding preferences of completely uncharacterized TFs, in the context of natural variation and disease, there is great interest in predicting the changes in DNA-binding specificities induced via single-amino acid alterations to wildtype TFs. Mutated TFs are seen in cancer (Kobren et al 2020), and in inherited diseases (Hamosh et al 2005;Chi 2006). If such an alteration occurs in a DNA-contacting residue, as a first approximation, de novo prediction is necessary only for the binding site positions contacted by that altered residue, while the specificity for the remaining binding site positions can be transferred directly from the wildtype.…”
Section: Resultsmentioning
confidence: 99%
“…While de novo DNA-binding specificity prediction is necessary for predicting binding preferences of completely uncharacterized TFs, in the context of natural variation and disease, there is great interest in predicting the changes in DNA-binding specificities induced via single-amino acid alterations to wildtype TFs. Mutated TFs are seen in cancer (Kobren et al . 2020), and in inherited diseases (Hamosh et al .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…While we have demonstrated the usefulness of our predictions for annotating DUF domains, our framework can be used for annotating many types of other protein domains, including assigning novel functions for already annotated domains. Moreover, knowledge of the specific sites within domains involved in interactions can help prioritize disease-causing mutations ( 16 , 62 ) and may result in identifying novel drug targets, as most drugs operate by competing for ligand-binding sites ( 63 ).…”
Section: Discussionmentioning
confidence: 99%
“…Recently, it has been shown that domains provide a framework within which to aggregate structural co-complex data and this per-domain aggregation allows accurate inference of positions within domains that participate in interactions ( 15 ). Domains annotated in this manner can then be used to identify interaction sites within proteins, and such domain-based annotation of interaction sites has been the basis of approaches to detect genes with perturbed functionalities in cancer ( 16 ) and to perform systematic cross-genomic analysis of regulatory network variation ( 17 ).…”
Section: Introductionmentioning
confidence: 99%